Intraventricular hemorrhage in premature infants under 28 weeks in general hospital of Lima, 2013 - 2017 - Espiritu Rojas, Elizabeth Ruth (2021)
Objective: To determine the incidence and clinical characteristics of intraventricular hemorrhage in premature infants younger than 28 weeks, born in a general hospital. Material and methods: This is an observational, retrospective cohort study, which included premature infants under 28 weeks gestational, who survived the first day of life and who had a brain ultrasound, born in the Cayetano Heredia Hospital from 2013 to 2017. Neonates with brain malformations and those with incomplete perinatal data were excluded. Results: During the study period, 21 722 newborns were born, of whom 84 were under 28 weeks of age, 72 children from 24 to 27 gestational weeks were included. The male / female ratio was 1.6. The HIV frequency was 58.3% (42/72). 52.4% (22/42) were found in the early form and 47.6% (20/42) in the late form. The severe degrees corresponded to 64% (27/42). Post hemorrhagic hydrocephalus occurred in 26% (11/42) and venous hemorrhagic infarction 21.4% (9/42). 51 patients died, with a fatality rate of 76.1% (32/42). Conclusions: HIV was very frequent, severe and lethal in premature babies <28 weeks, half of the cases occurred in the first three days and the rest during the first two weeks of life. Associated factors were lower birth weight, labor, and pneumothorax.